Emotional Intelligence and Physical Activity in College Students at UNWE - Stoyanova, Sevdalina; Markova, Zornitsa (Research Papers, 2023)
In light of the increasing hypodynamia, mental health problems and the influence of psychosocial factors in students, it is becoming increasingly important to understand the determining role of emotional intelligence in their motor performance. The problem of physical activity and emotions is particularly relevant after the global pandemic in 2020 and 2021. The aim of our study is to assess the emotional intelligence (EI) of students and its predictive nature on physical activity behavior (PA) among students. 190 college students from UNWE were studied. Emotionally aware students are found to be more physically active, and participating in FA can be an effective way to improve their physical, psychological and emotional health.